Human small intestine cancer cell membrane‐camouflaged quercetin‐melanin for antibacterial and antitumor activity. Issue 10 (8th February 2021) - Wang, Jingyuan; Cheng, Hao; Wang, Zekun; Yang, Endong; Guo, Feng; Wang, Weiyun; Sun, Dongdong
Abstract: E. coli has become an important factor that can lead to cancer because of its ability to cause diverse intestinal changes. Nano‐polymer materials provide ideal drug delivery systems for preparing antibacterial and anti‐cancer drugs because of their unique structure, easy modification, and high drug loading. The modified natural melanin has the potential to be an excellent nano‐carrier. By improving the water‐solubility and biocompatibility of the loaded natural drug quercetin, the antibacterial effect of quercetin can be fully played. Here, natural melanin was extracted from frozen squid to synthesize carrier polydopamine (PDA) nanoparticles, and the natural drug quercetin (Q) was modified on the surface of PDA by π‐π bond and covalent bond action to produce melanin‐quercetin (PDA‐Q). We also developed human small intestinal cancer cells (HIC) membrane‐camouflaged melanin‐Quercetin (PDA‐Q) nanoparticles as an anti‐cancer platform in vivo. The potential bacteriostatic mechanism was likely driven by the penetration of PDA‐Q in E. coli cells, damaging the integrity of the membranes of E. coli and inducing cell death. The mice wound experiment and bacteremia model experiment revealed that C@PDA‐Q had a strong inhibitory effect on E. coli in vivo. In addition, the results of the in vitro tumor test also revealed that C@PDA‐Q had strong anti‐tumor activity against HIC cells of human small intestinal cancer, and the IC50 value was 12.3 ± 0.7 μg/ml, which was slightly better than that for cisplatin. As both melanin nanoparticles and HIC membrane are natural biomaterials, the synthesized C@PDA‐Q nano‐polymer material shows great potential for use in anti‐cancer nano‐drug loading.